Answer:
12x + 2
Step-by-step explanation:
12 is multiplyed by both the x and the (1/6) since it is outside the equation.
so 12 times x = 12x since we dont know what x is
and 12 times (1/6) = (12/6) = 2
Answer:
7/4 +1/6 +X=15/2
1/6+X=15/2-7/4
1/6+X=30/4-7/4
X=23/4 - 1/6
X= 138-4/24
134/24
5.58333
Step-by-step explanation:
Answer: 46 years
Step-by-step explanation:
Let the father's age be x and the son's age be y, then 3 years ago:
Father = x - 3
son = y - 3
Then , from the first statement :
x - 3 = 3 ( y - 3 )
x - 3 = 3y - 9
x = 3y - 9 + 3
x = 3y - 6 .......................................... equation 1
In five years time
father = x + 5
son = y + 5
Then , from the second statement
x + 5 = 2 ( y + 5 )
x + 5 = 2y + 10
x = 2y + 10 - 5
x = 2y + 5 ........................ equation 2
Equating equation 1 and 2 , we have
3y -6 = 2y + 5
add 6 to both sides
3y = 2y + 5 + 6
subtract 2y from both sides
3y - 2y = 11
y = 11
substitute y = 11 into equation 1 to find the value of x
x = 3y - 6
x = 3(11) - 6
x = 33 - 6
x = 27
This means that the father is presently 27 years and the son is presently 11 years.
In four years time
father = 27 + 4 = 31
son = 11 + 4 = 15
sum of their ages in four years time will be
31 + 15 = 46 years
The answer is option .. A : 500(10) + 600(2)
I Just took the assignment and that is the Correct Answer :)